Desenvolvimento e aplicação da extração guiada por dispersão energizada (EDGE) na análise de capim limão, espinheiro branco e espinheira santa: estudo cromatográfico e determinação de atividades antioxidantes - Silva, Rosianne Pereira (2024)
Tea and herbal infusions are widely consumed and offer numerous health benefits, primarily due to their bioactive compounds. These compounds have powerful antioxidant properties that help prevent diseases and slow premature aging by neutralizing free radicals and oxygenated species that can damage cells. To fully harness these benefits, it is essential to accurately identify and measure bioactive compounds using advanced techniques that extract and concentrate them without degradation. Cutting-edge methods such as EDGE™, spectrophotometry, and High-Performance Liquid Chromatography (HPLC) are particularly effective in this process. This study optimized EDGE extraction to determine total phenolic compounds (TPC) in medicinal herbs using a Doehlert matrix with time and temperature variables. The optimization process was analyzed through Response Surface Methodology and ANOVA. The antioxidant activity in vitro of lemongrass, hawthorn, and espinheira santa extracts was evaluated using ABTS, DPPH, and FRAP assays, correlating the results with TPC values measured by the Folin-Ciocalteu method. Additionally, non-volatile analytes in the hydroethanolic extracts were identified and quantified using liquid chromatography with diode array detection. The TPC was 59.65 mg GAE/g in lemongrass, with HPLC UV-Vis/DAD identification of caffeic acid (15.01 μ L -1), p-coumaric acid (3.70 μ L-1), transferulic acid (16.49 μ L-1) and trans-3-hydroxycinnamic acid (3.06 μ L-1). In hawthorn, the TPC was 85.62 mg GAE/g, containing caffeic acid (10.98 μ L-1), p-coumaric acid (5.78 μ L-1), theophylline (6.37 μ L-1), and rutin (93.05 μ L-1). Finally, espinheira santa presented a TPC of 25.92 mg GAE/g of phenolics, with caffeic acid (14.59 μ L-1), p-coumaric acid (3.49 μ L-1), cinnamic acid (3.82 μ L-1) and theophylline (2.49 μ L-1). The combined evaluation of the antioxidant assays provided a comprehensive profile of the in vitro antioxidant activity of the extracts. In the ABTS assay, capture values were 55.71 ± 2.74 mg TE/g for lemongrass (CL), 19.5 ± 0.92 mg TE/g for espinheira santa (ES), and 82.41 ± 4.14 mg TE/g for hawthorn (EB). In the DPPH assay, the antioxidant capacities were 22.34 ± 0.1 mg TE/g (CL), 5.83 ± 0.55 mg TE/g (ES), and 54.64 ± 0.27 mg TE/g (EB). The reducing potential was highest in EB (1920.4 ± 66.39 mg TE/g), followed by ES (1216.3 ± 47.02 mg TE/g) and CL (1158.92 ± 29.87 mg TE/g). These results provide a comprehensive profile of the in vitro antioxidant activity of the extracts, highlighting their potential health benefits.